KARAKTERISTIK SENSORIS ROTI MANIS BERBASIS TEPUNG KOMPOSIT YANG DIFORTIFIKASI RUMPUT LAUT - . Kartiwan; Bachtaruddin Badewi (Politeknik Pertanian Negeri Kupang, 2009)
The experiment of Characteristics Sensoric of Sweet Bread on Composite Fl ourBases That Fortification by Seaweed was conducted at Food Technology Laboratory of Politani Negeri Kupang. The objective of the research are to get good comparison between composite flour and seaweed flour to produce good sensoric of sweet bread. The experiment was used RCBD design with factorial pattern. The factors were composite flour (0%, 10%, 20% and 30%), seaweed flour (0%, 5% and 10%) and 3 time replications. The seaweed cultivar used for fortification was Eucheuma cotonii. The respons were observed sensoric evaluation. The data varians was evaluated and continued by DMRT test. The result showed that the sensoric respons were (a) The panelist still interested on grain/cell colour, aroma, and flavour of sweet bread made of composite flour until 10% (b) The most of panelist interest on the texture (the soften) of sweet bread made of wheat flour base, (c) Fortification 5% and 10% of seaweed to the dough has a little affect of panelist interest to sweet bread. The prosfect sweet bread was the bread made of composite flour 10% and fortification of seaweed flour 10% has good quality. Key Words: fortification, composite flours, sensoric.